Tich Me Ar Tich Dem — Inception Report - Haßler, Björn; Lurvink, Anne-Fleur; Beoku-Betts, Iman; McBurnie, Chris; Adam, Taskeen; Blower, Tom (OpenDevEd, 2022)
Our research addresses the Sierra Leonean government’s need to optimise and validate an effective model for in-service TPD. As noted, a distributed TPD model is favoured (building on the World Bank’s Free Education project and the Sierra Leone Education Attendance Monitoring System (SLEAMS), using a ‘one-tablet-per-school’ (OTPS) model). Evidence indicates that this low-tech approach to TPD can improve learning outcomes in emergencies (⇡Haßler, et al., 2019). In contrast, COVID-19 interventions that focus on ‘remote learning for children’ are catastrophically failing (⇡Asadullah, 2020; ⇡Asanov, et al., 2020; ⇡BRAC, 2020; ⇡Le Nestour, et al., 2020; ⇡Uwezo Kenya, 2020). Our research provides crucial and timely evidence to shore up current government plans for a scalable, effective TPD intervention. Our research identifies whether this TPD model addresses the needs of rural / disadvantaged teachers. Our study focuses on a sample of teachers and students from schools in rural / semi-rural areas to understand whether and how school-based TPD initiatives promote student learning (as an alternative to traditional centralised and cascade models). Such traditional models are severely disrupted by COVID-19, highlighting our study’s relevance to education continuity in emergencies.
ZenodoArchiveID: 6335781 ZenodoArchiveConcept: 6335780 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0268 10.53832/opendeved.0269 2129771:3RTBA9FR
Keywords: Author:OpenDevEd; AuthorFirst:Haßler; _bjoern_cv; _r:AddedByZotZen; _yl:b